Sodium-ion battery coating and rolling process for preventing negative electrode from sticking to roller

By performing optimization measures such as slurry screening, controlling the coating speed and rolling in two times in the coating roller process of sodium ion battery, the problem of the negative electrode rolling of sodium ion battery is easily sticky in the roller pressing process, and the production efficiency and battery performance are improved.

CN119588581APending Publication Date: 2025-03-11HUNAN FENGRI ELECTRIC GROUP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411714711.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The negative electrode roll of sodium ion battery is prone to sticking roller problems during the rolling process, which affects production efficiency and product quality.

Method used

A sodium ion battery coating rolling process is adopted to prevent the negative electrode from sticking to the roller, including slurry sieving, controlling the coating speed, online baking, vacuum drying, fan cooling and rolling in two times, to optimize the process to avoid sticking to the roller.

Benefits of technology

It effectively avoids the problems of sticking, powder loss and wrinkling during the negative roller pressing of sodium ion battery, improves production efficiency, and ensures the good first-term effect and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588581A_ABST
    Figure CN119588581A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion battery production processes, in particular to a sodium ion battery coating and rolling process for preventing a negative electrode from sticking to a roller, which comprises the following steps: performing magnetic filtration and secondary sieving on negative electrode slurry, pumping the secondarily sieved negative electrode slurry into a coating machine for coating, and controlling the coating speed of the negative electrode to be 30 + / -10m / min; carrying out continuous online baking on the coated negative electrode by adopting a baking oven to obtain a negative electrode roll; drying the negative electrode roll in a vacuum oven; cooling the negative electrode roll dried by the vacuum oven; and rolling the cooled negative electrode roll twice by using a roller press. By adopting the process disclosed by the invention, the problems of roll sticking, powder falling, wrinkling and the like of the sodium-ion battery in the negative electrode rolling process can be greatly reduced, and the prepared sodium-ion battery has relatively good first effect and cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion battery production technology, and in particular to a sodium ion battery coating roller pressing process for preventing negative electrodes from sticking to rollers. Background Art

[0002] As the main component of sodium-ion batteries, the quality of battery pole pieces directly affects battery performance and yield. Sodium-ion battery pole pieces are made of aluminum foil as a substrate, coated with hard carbon and other active materials, and then rolled and slit to complete the production. Rolling is to improve the battery energy density, electronic conductivity and compaction thickness, etc., and is one of the most important processes before battery pole pieces are formed.

[0003] Roller sticking is a process problem that occurs during the rolling process. It is manifested as the active material coated on the current collector adheres to the surface of the roller during the rolling process. It not only affects industrial production efficiency, but may also lead to a decrease in product quality. Therefore, understanding and solving the problem of roller sticking is an important part of industrial production. In actual production, the phenomenon of roller sticking may be caused by a variety of factors, including differences in slurry particle radius, roller temperature, rolling pressure, baking temperature, and processing environment.

[0004] In the production of sodium-ion batteries, the coating slurry in the negative electrode roll is composed of hard carbon active materials and water-based slurry. Therefore, compared with the positive electrode rolling, the negative electrode rolling will more frequently cause problems such as sticking to the roller and falling powder, which seriously affects production efficiency and product quality. In the existing process, the method for dealing with roller sticking is often to stop the machine to clean the roller, or send the electrode to a vacuum oven for baking after coating. This practice delays production efficiency and consumes a lot of energy, so there is an urgent need to optimize the process. Summary of the invention

[0005] In order to solve the technical problem that the negative electrode of the sodium ion battery is easy to stick to the roller during the rolling process, the present invention provides a sodium ion battery coating rolling process for preventing the negative electrode from sticking to the roller, and the prepared sodium ion battery has good initial efficiency and cycle life.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0007] A sodium ion battery coating roller pressing process for preventing negative electrode from sticking to roller comprises the following steps:

[0008] A1. Slurry screening: Before starting the coating process, the negative electrode slurry is magnetically filtered and screened twice, and the mesh size used is 100-250 mesh;

[0009] A2. Pump the negative electrode slurry after secondary screening into the coating machine for coating, and control the negative electrode coating speed at 30±10m / min;

[0010] A3. The coated negative electrode coil is continuously baked online in an oven, and the oven is divided into three zones according to the number of ovens, namely, a temperature rise zone, a constant high temperature zone, and a constant low temperature zone;

[0011] A4. Place the negative electrode coil after online baking into a vacuum oven for drying;

[0012] A5. Place the negative electrode coil dried in the vacuum oven in the cooling area and use a fan to cool the negative electrode coil;

[0013] A6. Roll the negative electrode coil after cooling twice using a roller press.

[0014] Furthermore, in step A1, the mesh size of the sieve used is 150 to 200 meshes.

[0015] Furthermore, in step A2, the negative electrode coating speed is controlled at 30±2.0 m / min.

[0016] Furthermore, in step A3, the starting temperature of the heating interval is 70°C, the final temperature is 100°C, and the blowing frequency is 25Hz; the temperature of the constant high temperature baking interval is 110°C, and the blowing frequency is 35Hz; the temperature of the constant low temperature baking interval is 70°C, and the blowing frequency is 20Hz.

[0017] Furthermore, in step A4, the oven temperature is set to 90-100° C., and the vacuum degree is -0.091-0.098 MPa.

[0018] Furthermore, in step A5, the blowing frequency of the fan is 30±10 Hz, and the temperature of the negative electrode coil after cooling is ≤40°C.

[0019] Furthermore, in step A6, the compaction density of the negative electrode during roller pressing is 0.95 to 0.97 g / cm 3 The rolling is carried out twice, the first rolling pressure is 80% of the design pressure, and the second rolling pressure is 90% of the design pressure.

[0020] The beneficial effects of the present invention include:

[0021] The main reasons for the negative electrode sticking during rolling of sodium ion batteries include: insufficient drying of the electrode during coating, too long baking in a vacuum oven, the influence of the type of negative electrode material, the influence of the stirring and coating process, and too high compaction density (rolling pressure). Therefore, the present invention optimizes the process for the above reasons that lead to sticking.

[0022] Since hard carbon used for sodium ion negative electrode active materials is difficult to disperse and easy to agglomerate, flocculent agglomerates are very likely to appear in the stirring process, causing abnormal surface density of the pole piece during coating, which in turn leads to local overpressure during rolling, and problems of sticking to the roller and falling powder. The present invention adds a secondary screening after the conventional magnetic filtration process and before the coating process, using a screen with a preferred mesh size of 150 to 200, which can better filter the flocculent.

[0023] In the coating process, slowing down the coating speed and adopting the preferred 30±2.0m / min can prolong the time the pole piece stays in the oven and make the pole piece more fully baked. At the same time, the oven is divided into three zones according to the number; when the pole piece passes through the heating zone, it undergoes a gradual heating process, and is blown by 25Hz low-speed hot air at the same time, and then enters the constant temperature, 110℃ high temperature 35Hz high-frequency wind speed baking zone. The purpose of setting the heating zone is to preheat the pole piece so that the pole piece can be dried more evenly from the inside to the outside in the next stage of baking, avoiding the uneven heating speed of the pole piece surface and the inside due to the high temperature when the pole piece enters the oven, which causes the binder and solvent to volatilize too quickly, resulting in the formation of a step-by-step increase in the binder concentration from the foil to the pole piece surface, and finally avoiding the sticking roller problem caused by the adhesion between the pole piece surface and the negative electrode material being greater than the adhesion between the foil and the negative electrode material. The significance of setting a constant low temperature range is to allow the electrode to completely dry and the adhesive to completely wrap the active material, and then to solidify the adhesive by cooling to obtain a better bonding effect.

[0024] The purpose of step A5 is to use a fan to accelerate the cooling of the negative electrode coil that has been vacuum-baked, thereby shortening the overall rolling process time and ensuring that the negative electrode coil can be rolled at a lower temperature, thereby better preventing the foil from sticking to the roller due to excessive temperature.

[0025] The purpose of step A6 is that, since the negative electrode active material of the sodium ion battery adopts hard carbon, a large pressure is required during rolling to achieve the designed compaction density, and excessive pressure during rolling is more likely to cause roller sticking. Therefore, when rolling the negative electrode of the sodium ion battery, the rolling is divided into two times, the first rolling adopts 80% of the design pressure, and the second rolling adopts 90% of the design pressure, which can ensure that the designed compaction density is achieved while avoiding excessive single pressure.

[0026] In summary, the beneficial effects of the present invention include:

[0027] The present invention provides a sodium ion battery coating roller pressing process that prevents negative electrode sticking to the roller. Without adding or significantly changing the process, a multi-pronged approach is adopted to optimize the problems existing in each previous process rather than a single process, so as to better avoid the problem of sticking to the roller. By adopting the present invention, the problems of sticking to the roller, powder loss, wrinkles, etc. of the sodium ion battery during the negative electrode rolling process are greatly reduced, and at the same time, the overall production efficiency is ensured to be least affected; and the manufactured sodium ion battery has a good first effect and cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a process flow chart of the present invention;

[0029] Figure 2 This is a SEM image of the negative electrode sheet of the sodium ion battery prepared in Example 1;

[0030] Figure 3 The following are the cycle test results of the sodium ion batteries prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0031] In order to make the objectives, technical solutions and advantages of the present invention more clear, the technical solutions of the present invention are further described in detail below in conjunction with specific implementation methods.

[0032] Example 1

[0033] A sodium ion battery coating roller pressing process for preventing negative electrode from sticking to roller comprises the following steps:

[0034] A1. Slurry screening: Before starting the coating process, the negative electrode slurry is subjected to conventional magnetic filtration and secondary screening, and the mesh size used is 150 mesh;

[0035] A2. Pump the negative electrode slurry after secondary screening into the coating machine for coating, and control the negative electrode coating speed at 32m / min;

[0036] A3. The coated negative electrode coil is baked continuously online in an oven. The oven is divided into three sections according to the number of ovens, namely, a heating section, a constant high temperature section and a constant low temperature section. The starting temperature of the heating section is 70°C, the final temperature is 100°C, and the blowing frequency is 25Hz. The temperature of the constant high temperature baking section is 110°C, and the blowing frequency is 35Hz. The temperature of the constant low temperature baking section is 70°C, and the blowing frequency is 20Hz.

[0037] A4. Place the negative electrode coil after online baking into a vacuum oven for drying. The oven temperature is set to 90-100°C and the vacuum degree is -0.091-0.098MPa.

[0038] A5. Place the negative electrode coil dried in the vacuum oven in the cooling area and use a fan with a blowing frequency of 30±10Hz to cool the electrode so that the temperature of the electrode is ≤40℃ after cooling.

[0039] A6. The negative electrode coil after cooling is rolled twice by a roller press. The first rolling pressure is 80% of the design pressure, and the second rolling pressure is 90% of the design pressure. The design compaction density is 0.96g / cm3.

[0040] After the above steps, the negative electrode sheet of the sodium ion battery is obtained, and the flow chart is as follows: Figure 1 As shown, its SEM image is as follows Figure 2 shown.

[0041] Example 2

[0042] A sodium ion battery coating roller pressing process for preventing negative electrode from sticking to roller comprises the following steps:

[0043] A1. Slurry screening: Before starting the coating process, the negative electrode slurry is subjected to conventional magnetic filtration and secondary screening, and the mesh size used is 100 mesh;

[0044] A2. Pump the negative electrode slurry after secondary screening into the coating machine for coating, and control the negative electrode coating speed at 30m / min;

[0045] A3. The coated negative electrode coil is baked continuously online in an oven. The oven is divided into three sections according to the number of ovens, namely, a heating section, a constant high temperature section and a constant low temperature section. The starting temperature of the heating section is 70°C, the final temperature is 100°C, and the blowing frequency is 25Hz. The temperature of the constant high temperature baking section is 110°C, and the blowing frequency is 35Hz. The temperature of the constant low temperature baking section is 70°C, and the blowing frequency is 20Hz.

[0046] A4. Place the negative electrode coil after online baking into a vacuum oven for drying. The oven temperature is set to 90-100°C and the vacuum degree is -0.091-0.098MPa.

[0047] A5. Set up a static cooling area and use a fan with a blowing frequency of 30±10Hz to cool the electrode so that the temperature of the electrode is ≤40℃ after static cooling;

[0048] A6 performs negative electrode roller pressing twice. The first roller pressing pressure is 80% of the design pressure, and the second roller pressing pressure is 90% of the design pressure. The design compaction density is 0.96 g / cm 3 .

[0049] Example 3

[0050] A sodium ion battery coating roller pressing process for preventing negative electrode from sticking to roller comprises the following steps:

[0051] A1. Slurry screening: Before starting the coating process, the negative electrode slurry is magnetically filtered and screened twice, and the mesh size used is 150 mesh;

[0052] A2. Pump the negative electrode slurry after secondary screening into the coating machine for coating, and control the negative electrode coating speed at 40m / min;

[0053] A3. The coated negative electrode coil is baked continuously online in an oven. The oven is divided into three sections according to the number of ovens, namely, a heating section, a constant high temperature section and a constant low temperature section. The starting temperature of the heating section is 80°C, the final temperature is 110°C, and the blowing frequency is 35Hz. The temperature of the constant high temperature baking section is 110°C, and the blowing frequency is 35Hz. The temperature of the constant low temperature baking section is 70°C, and the blowing frequency is 20Hz.

[0054] A4. Place the negative electrode coil after online baking into a vacuum oven for drying. The oven temperature is set to 90-100°C and the vacuum degree is -0.091-0.098MPa.

[0055] A5. Set up a static cooling area and use a fan with a blowing frequency of 30±10Hz to cool the electrode so that the temperature of the electrode after static cooling is ≤40℃;

[0056] A6. Perform negative electrode roller pressing twice. The first roller pressing pressure is 80% of the design pressure, and the second roller pressing pressure is 90% of the design pressure. The design compaction density is 0.96g / cm 3 .

[0057] Example 4

[0058] A sodium ion battery coating roller pressing process for preventing negative electrode from sticking to roller comprises the following steps:

[0059] A1. Slurry screening: Before starting the coating process, the negative electrode slurry is magnetically filtered and screened twice, and the mesh size used is 150 mesh;

[0060] A2. Pump the negative electrode slurry after secondary screening into the coating machine for coating, and control the negative electrode coating speed at 32m / min;

[0061] A3. The coated negative electrode coil is baked continuously online in an oven. The oven is divided into three sections according to the number of ovens, namely, a heating section, a constant high temperature section and a constant low temperature section. The starting temperature of the heating section is 70°C, the final temperature is 100°C, and the blowing frequency is 25Hz. The temperature of the constant high temperature baking section is 110°C, and the blowing frequency is 35Hz. The temperature of the constant low temperature baking section is 70°C, and the blowing frequency is 20Hz.

[0062] A4. Place the negative electrode coil after online baking into a vacuum oven for drying. The oven temperature is set to 90-100°C and the vacuum degree is -0.091-0.098MPa.

[0063] A5. Set up a static cooling area and use a fan with a blowing frequency of 30±10Hz to cool the electrode so that the temperature of the electrode after static cooling is ≤40℃;

[0064] A6. Perform negative electrode roller pressing twice. The first roller pressing pressure is 85% of the design pressure, and the second roller pressing pressure is 95% of the design pressure. The design compaction density is 0.96g / cm 3 .

[0065] Comparative Example 1

[0066] A sodium ion battery coating roller pressing process for preventing negative electrode from sticking to roller comprises the following steps:

[0067] A1. Before starting the coating process, the negative electrode slurry is magnetically filtered;

[0068] A2. Coating speed control: Control the negative electrode coating speed at 50m / min;

[0069] A3, the oven is not divided into zones, the baking temperature is 110°C, and the blowing frequency is 35Hz;

[0070] A4. Place the baked negative electrode coil in a vacuum oven for drying. The oven temperature is set to 90-100°C and the vacuum degree is -0.091-0.098MPa.

[0071] A5. Set up a static cooling area and use a fan with a blowing frequency of 30±10Hz to cool the electrode so that the temperature of the electrode after static cooling is ≤40℃;

[0072] A6. The negative electrode rolling operation is completed in one step, and the designed compaction density is 0.96g / cm3.

[0073] Pole piece adhesion test

[0074] Take a section of the electrode of each of the four embodiments and the electrode of comparative example 1, divide the electrode into small squares of equal size, observe the electrode first, then wipe the above four electrode sheets with filter paper, weigh the mass of the filter paper and the electrode, respectively, and measure the damaged area of ​​the electrode. The experimental results are shown in Table 1 below.

[0075]

[0076]

[0077] Table 1

[0078] Table 1 above is a comparison of the degree of damage to the pole pieces in Example 1, Example 2, Example 3, Example 4, and Comparative Example 1. It can be clearly found that after adopting the present invention, the pole piece exhibits relatively good peel strength, and there is no obvious shine caused by overpressure and spots caused by floccules in the slurry. Its performance is better than that of Comparative Example 1, proving that the present invention can well maintain the bonding effect between the active material and the current collector, improve the problems of sticking to the roller and powder falling, and improve the performance of the finished sodium ion battery.

[0079] Battery performance test

[0080] The negative electrode samples prepared in Example 1 and Comparative Example 1 were assembled into button cells with sodium sheets and electrolytes for the first week charge and discharge test and cycle performance test. The experimental results are shown in Table 2 below.

[0081] 1. First week charge and discharge test

[0082] The assembled battery was tested on a button battery tester under the following test conditions: let it stand for 2 hours, discharge it to 0V at a constant current of 0.1C at 25°C, let it stand for 5 minutes, and charge it to 2.5V at a constant current of 0.1C.

[0083] 2. Cycle performance test

[0084] The assembled battery was tested on a button battery cycle tester under the following test conditions: let it stand for 2 hours, discharge at a constant current of 0.1C to 0V at 25°C, leave it for 30 minutes, charge at a constant current of 0.1C for 150 minutes to 2.5V, and then charge at a constant voltage to 3.2V; discharge at a constant voltage of 0.1C to the cut-off voltage, and finally leave it for 30 minutes.

[0085] Repeat this cycle 500 times to check the battery capacity retention rate.

[0086]

[0087] Table 2

[0088] Table 2 above shows the first charge and discharge and cycle performance test results of the button-type battery assembled with the pole pieces made in Example 1 of the present invention and Comparative Example 1 at a rate of 0.1C. By comparison, it can be seen that the battery corresponding to Example 1 of the present invention exhibits better electrochemical performance, and its first charge and discharge capacity, first coulomb efficiency, and capacity retention rate after 500 cycles are higher than those using the conventional rolling method. The reason is that in the pole piece production stage, the secondary rescreening of the slurry reduces the number of floccules and large particles, thereby reducing the occurrence of sodium precipitation during battery operation, and is beneficial to the formation of SEI film; the rolling is divided into two times to avoid the problem of excessive compression of the negative electrode active material due to excessive rolling pressure, which can better promote ion flow and electrolyte penetration. In summary, the electrochemical performance of the battery is improved overall.

[0089] The above is only a preferred embodiment of the present invention, but the protection scope of the present invention is not limited thereto. The present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A sodium ion battery coating roller pressing process for preventing negative electrode from sticking to roller, characterized in that: The process includes the following steps: A1. Slurry screening: Before starting the coating process, the negative electrode slurry is magnetically filtered and screened twice, and the mesh size used is 100-250 mesh; A2. Pump the negative electrode slurry after secondary screening into the coating machine for coating, and control the negative electrode coating speed at 30±10m / min; A3. The coated negative electrode is continuously baked online in an oven. The oven is divided into three zones according to the number of ovens, namely, a temperature rise zone, a constant high temperature zone and a constant low temperature zone. After baking, the negative electrode is rolled up by a coating machine to obtain a negative electrode roll; A4. Place the negative electrode coil in a vacuum oven for drying; A5. Place the negative electrode coil dried in the vacuum oven in the cooling area and use a fan to cool the negative electrode coil; A6. Roll the negative electrode coil after cooling twice using a roller press.

2. The sodium ion battery coating roller pressing process for preventing negative electrode from sticking to roller according to claim 1, characterized in that: In the step A1, the mesh size of the sieve used is 150 to 200 meshes.

3. The sodium ion battery coating roller pressing process for preventing negative electrode from sticking to roller according to claim 1, characterized in that: In the step A2, the negative electrode coating speed is controlled at 30±2.0 m / min.

4. The sodium ion battery coating roller pressing process for preventing negative electrode from sticking to roller according to claim 1, characterized in that: In step A3, the starting temperature of the heating interval is 70°C, the final temperature is 100°C, and the blowing frequency is 25Hz; the temperature of the constant high temperature baking interval is 110°C, and the blowing frequency is 35Hz; the temperature of the constant low temperature baking interval is 70°C, and the blowing frequency is 20Hz.

5. The sodium ion battery coating roller pressing process for preventing negative electrode from sticking to roller according to claim 1, characterized in that: In step A4, the oven temperature is set to 90-100° C., and the vacuum degree is -0.091-0.098 MPa.

6. The sodium ion battery coating roller pressing process for preventing negative electrode from sticking to roller according to claim 1, characterized in that: In step A5, the blowing frequency of the fan is 30±10 Hz, and the temperature of the negative electrode coil after cooling is ≤40°C.

7. The sodium ion battery coating roller pressing process for preventing negative electrode from sticking to roller according to claim 1, characterized in that: In step A6, the compaction density of the negative electrode during roller pressing is 0.95 to 0.97 g / cm 3 The rolling is carried out twice, the first rolling pressure is 80% of the design pressure, and the second rolling pressure is 90% of the design pressure.